Trace elements uptake by metal accumulator species grown on mine tailings amended with three types of biochar. - Fellet G; Marmiroli M; MARCHIOL, Luca (Science of The Total Environment, 2014)
Mine tailings are of great concern due to the risk their toxic inorganic elements pose to the environment. The application of biochar as an amendment may be a solution to reduce the risk of pollutant diffusion. The main purpose of the research was to verify the effects of different types of biochar produced from different feedstocks (pruning residues, fir tree pellets and manure pellets) on changing the substrate conditions to promote plant growth for the phytostabilization of mine tailings. The SEM/EDX characterization showed different structures in terms of porosity and granulosity as well as the element composition. The plants used in the pot experiment were Anthyllis vulneraria subsp. polyphylla (Dc.) Nyman, Noccaea rotundifolium (L.) Moench subsp. cepaeifolium and Poa alpina L. subsp. alpina. The biochars were applied at three doses: 0, 1.5 and 3%dw. Although to different extents, the biochars induced significant changes of the substrates in terms of pH, EC, CEC and bioavailability of themetals. The biochar frommanure pellets and pruning residues reduced shoot Cd and Pb accumulations. The former also led to a higher biomass production that peaked at the1.5% dose. Biochar has great potential as an amendment for phytoremediation but its effects depend on the type of feedstock it derives from. The characteristics of the substrate to be treated are crucial for the biochar selection.